2016
DOI: 10.7589/2014-05-121
|View full text |Cite
|
Sign up to set email alerts
|

Polymelia and Syndactyly in a Swainson’s Hawk (Buteo swainsoni)

Abstract: A hatch-year Swainson's Hawk (Buteo swainsoni) recovered from Modoc County, California, US, on 12 August 2012 had malformations of the rear limbs consisting of bilateral polymelia and syndactyly. We describe the malformations and evaluate potential causes. Postmortem examination revealed varus rotation of both femurs and abnormal appendages originating from the distal medial surface of the tibiotarsi with two nonfunctional digits on the right leg and one digit on the left leg. There was syndactyly between digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…Polymelia has been reported in amphibians (Hassine et al, 2011), cattle (Muirhead et al, 2014;Kim et al, 2001;Barua et al, 2014), birds (Rogers et al, 2016;Abu-Seida, 2014), and domestic dogs (Daneze and Brasil, 2018), as well as in humans (Retnam et al, 2016). However, to the knowledge of the authors, it has never been reported in opossums.…”
Section: Case Historymentioning
confidence: 99%
“…Polymelia has been reported in amphibians (Hassine et al, 2011), cattle (Muirhead et al, 2014;Kim et al, 2001;Barua et al, 2014), birds (Rogers et al, 2016;Abu-Seida, 2014), and domestic dogs (Daneze and Brasil, 2018), as well as in humans (Retnam et al, 2016). However, to the knowledge of the authors, it has never been reported in opossums.…”
Section: Case Historymentioning
confidence: 99%
“…This description fits polymelia, a congenital disease consisting of the presence of a supernumerary limb. Its causes are not well known and it is thought that different genetic, teratological factors (pollutants, UV radiation or exposure to chemical or radioactive substances), environmental stress, poor nutrition or the action of parasites could be involved (Hays & Risebrough 1972, Albers et al 2001, Pourlis 2011, Rogers et al 2016, Onmus et al 2017, Perin 2017, Klingler & Glasmann 2019. This anatomical malformation is known in humans and vertebrate animals, especially domestic animals and anurans, but it is very rare in other wildlife groups.…”
mentioning
confidence: 99%
“…Unlike farmed birds, where it is commonplace (Pourlis 2011, Hirschberg et al 2012, polymelia in wild birds is exceptionally rare. The scientific bibliography contains only 15 described cases of polymelia in birds, specifically in American Robin Turdus migratorius (Shufeldt 1919), House Sparrow Passer domesticus (Stoneman 1932), Mourning Dove Zenaida macroura (Frankowiak 1962, Robbins & Pokras 1995, Common Tern Sterna hirundo (Hays & Risebrough 1972), Cattle Tyrant Machetornis rixosa (Lopes et al 1981), Eastern Screech-owl Otus asio (Albers et al 2001), King Penguin Aptenodytes patagonicus (Voisin et al 2002), White-crowned Sparrow Zonotrichia leucophrys (Schiller et al 2007), Swainson's Hawk Buteo swainsoni (Rogers et al 2016), White Stork Ciconia ciconia (Onmus et al 2017), Jackass Penguin Spheniscus demersus (Vanstreels et al 2018, Snyman et al 2022, Silver Gull Chroicocephalus novaehollandiae (Woehler & Holzmann 2020) and Pied Flycatcher Ficedula hypoleuca (Fuertes-Recuero et al 2023). Polymelia is sometimes confused with polydactyly, a pathology in which the fingers of the limbs are duplicated that frequently appears in birds such as raptors, waders, Psittaciformes, Caprimulgiformes or Apodiformes (Chandler 1992, Frey et al 2001, Crosta et al 2002, Dogliero et al 2018.…”
mentioning
confidence: 99%
“…So far, it has been reported among broiler chickens and other farming fowls (Abu-Seida 2014, Hassanzadeh & Rahemi 2017, Plang et al 2021, Snyman et al 2022). The only cases reported in wild birds are the Swainson's Hawk Buteo swainsoni (Rogers et al 2016) and the White Stork Ciconia ciconia (Onmuş 2017). However, in contrast with polymelia, polydactyly, which is defined as the presence of extra digit(s), is reported more frequently (Hollander & Levi 1942, Sakai 2006), and has been described in association with cases of polymelia (Onmuş 2017, Woehler & Holzmann 2020).…”
mentioning
confidence: 99%